Variações no diagnóstico in vitro e abordagem terapêutica de lesões de cárie por cirurgiões-dentistas em Fortaleza-CE - Lotif, Mara Assef Leitão (2017)
Purpose: The aim of this study was to identify the variation of caries diagnosis and its relationship with treatment planning, as well as to verify the variation of the diagnosis when using interproximal radiographs or not, through an electronic questionnaire with clinical and radiographic images. Materials and methods: The electronic questionnaire was elaborated with clinical and radiographic images of 10 extracted human molars without defects such as hypoplasias and showing occlusal pits and fisures that could lead to some kind of doubt regarding the presence of caries. Afterwards, histological slides were prepared with sections of the region possibly affected by caries and observed under optical microscopy to validate caries diagnosis. The questionnaire was applied to 159 dentists of both genders, working in primary care in Fortaleza-CE city. The percentage of correct diagnosis for visual examination and visual examination associated with radiography was calculated and the diagnosis provided by the participants and their respective therapeutic options was related. Results: The association of interproximal radiography with visual examination did not influence the detection of enamel caries, however, it contributed significantly to the detection of dentin lesions. Therapeutic indications for the diagnoses provided by participants demonstrated a tendency to overtreating sound teeth and those with enamel caries. Conclusion: The findings of this study raise the need for retraining dental surgeons regarding the caries diagnosis and current therapeutic approaches.